AB0822 Therapeutic Response in Adalimumab-Treated Patients with Psoriatic Arthritis in Relation to Weight. (9th June 2015) - Mease, P.; Gladman, D.D.; Ritchlin, C.T.; Warren, R.B.; Rubant, S.; Li, Y.; Dorr, A.P.; Anderson, J.K.
Abstract : Background: In the Adalimumab Effectiveness in Psoriatic Arthritis Trial (ADEPT), elevated CRP was shown to predict radiographic progression. 1 It is not known if CRP has a predictive role in the clinical response to adalimumab (ADA) treatment; however, it is known that obesity is related to subclinical inflammation as measured by CRP and that psoriatic arthritis (PsA) patients (pts) tend to be obese. Objectives: To evaluate the effect of weight (wt) on clinical response in PsA pts treated with ADA Methods: ADEPT was a 24-week (wk) double-blind, randomized, placebo-controlled trial in pts with PsA and inadequate response to NSAIDs. In this post hoc analysis, wt was categorized by quartiles (Q). For each wt and CRP category, wk 12 endpoints were analyzed: Clinical Disease Activity Index (CDAI), Psoriatic Arthritis Response Criteria (PsARC), Psoriasis Area & Severity Index (PASI) 75 response, and Health Assessment Questionnaire (HAQ). Multivariate analysis was done for wk 12 endpoints accounting for wt quartile and CRP category in the model. Results: 309/313 pts enrolled had data available. Overall mean wt was 85.8 kg. Wt ranges (kg) per Q were: Q1=45.4–73.0, Q2=73.0–84.4, Q3=85.0–96.2, and Q4=97.0–156.0. CRP was elevated in 242/309 (78.3%). Pts with elevated CRP (%) in each wt Q was: Q1=67.5, Q2=75.3, Q3=85.2, Q4=84.6 ( P =0.021). Wt was weakly correlated with CRP at baseline (BL) using non-parametric testing (Kendall Tau b r=0.131, P =0.006). Mean wt was higher in the elevated vs normal CRP group (87.6 kg vs 79.4 kg, P =0.0012). Mean wt (kg) in the elevated CRP group by Q was: Q1=64.6, Q2=78.7, Q3=90.7, Q4=109.7. BL disease activity (tender joint count, swollen joint count, physician and pt global assessment of disease activity, CDAI, PASI, HAQ) was slightly higher in the elevated CRP group. For all outcome measures (CDAI, PsARC (Figure ), PASI75, and HAQ) treatment effect was in favor of ADA and no significant difference in treatment effect was observed across wt groups. In pts with both normal (n=67) and elevated (n=242) CRP statistically significant response in favor of ADA was observed for PASI75, with numerically superior but statistically nonsignficant results for CDAI, PsARC, and HAQ in pts with normal CRP. Wt group and CRP were not significant in the multivariate model. For CDAI, PsARC, and HAQ, treatment was statistically significant in favor of ADA regardless of wt or CRP. Sample sizes were too small to make meaningful conclusions for PASI. Conclusions: The majority of PsA pts in ADEPT had an elevated CRP indicating a general inflammatory state. Overall, ADA-treated pts had superior response rates compared to PBO-treated pts regardless of wt or CRP category. A limitation of this assessment is that wt was used as a surrogate for BMI as pt height was not available. References: Gladman DD et al. Arthritis Res Ther. 2010;12:R113. Acknowledgements: AbbVie funded the study (NCT00646386 ), contributed to its design and was involved in the collection, analysis, and interpretation of the data, and in the writing, review, and approval of the publication. Medical writing support was provided by Kathleen V. Kastenholz, PharmD, MS, of AbbVie. Disclosure of Interest: P. Mease Grant/research support from: AbbVie, Amgen, Biogen Idec, Bristol-Myers Squibb, Genentech, GlaxoSmithKline, Janssen Lilly, Merck, Merck Serono, Novartis, Novo Nordisk, Pfizer, Roche, UCB, and Vertex, Consultant for: AbbVie, Amgen, Biogen Idec, Bristol-Myers Squibb, Genentech, GlaxoSmithKline, Janssen Lilly, Merck, Merck Serono, Novartis, Novo Nordisk, Pfizer, Roche, UCB, and Vertex, Speakers bureau: AbbVie, Amgen, Biogen Idec, Bristol-Myers Squibb, Genentech, GlaxoSmithKline, Janssen Lilly, Merck, Merck Serono, Novartis, Novo Nordisk, Pfizer, Roche, UCB, and Vertex, D. Gladman Grant/research support from: AbbVie, Amgen, BMS, Celgene, Eli Lily, Janssen, Novartis, Pfizer, and UCB, Consultant for: AbbVie, Amgen, BMS, Celgene, Eli Lily, Janssen, Novartis, Pfizer, and UCB, C. Ritchlin Grant/research support from: Amgen, Janssen, Pfizer, and UCB, and consulting fees from AbbVie, Amgen, Janssen, Lilly, Pfizer, and UCB, R. Warren Grant/research support from: Abbvie, Amgen, Eli Lilly, GlaxoSmithKline, Janssen, Leo, Novartis, and Pfizer, Consultant for: Abbvie, Amgen, Eli Lilly, GlaxoSmithKline, Janssen, Leo, Novartis, and Pfizer, Speakers bureau: Abbvie, Amgen, Eli Lilly, GlaxoSmithKline, Janssen, Leo, Novartis, and Pfizer, S. Rubant Shareholder of: AbbVie, Employee of: AbbVie, Y. Li Shareholder of: AbbVie, Employee of: AbbVie, A. Dorr Shareholder of: AbbVie, Employee of: AbbVie, J. Anderson Shareholder of: AbbVie, Employee of: AbbVie